2011
DOI: 10.1136/thoraxjnl-2011-200508
|View full text |Cite
|
Sign up to set email alerts
|

uPAR regulates bronchial epithelial repair in vitro and is elevated in asthmatic epithelium

Abstract: BackgroundThe asthma-associated gene urokinase plasminogen activator receptor (uPAR) may be involved in epithelial repair and airway remodelling. These processes are not adequately targeted by existing asthma therapies. A fuller understanding of the pathways involved in remodelling may lead to development of new therapeutic opportunities. uPAR expression in the lung epithelium of normal subjects and patients with asthma was investigated and the contribution of uPAR to epithelial wound repair in vitro was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 36 publications
8
76
0
1
Order By: Relevance
“…(Portelli et al, 2014). This fits well with the observation of elevated levels of PLAUR in the airway epithelium in asthma patients (Stewart et al, 2012) and association of PLAUR levels with worsening prognosis and increased disease aggressiveness in other diseases such as cancer and COPD (Ivancso et al, 2013;Smith & Marshall, 2010). However it is difficult to infer completely the functional role of the gene with an overexpression approach and gene depletion is potentially more informative from this perspective.…”
Section: The Spatial Organization Of Chromosomes: Chromosome Conformasupporting
confidence: 75%
See 1 more Smart Citation
“…(Portelli et al, 2014). This fits well with the observation of elevated levels of PLAUR in the airway epithelium in asthma patients (Stewart et al, 2012) and association of PLAUR levels with worsening prognosis and increased disease aggressiveness in other diseases such as cancer and COPD (Ivancso et al, 2013;Smith & Marshall, 2010). However it is difficult to infer completely the functional role of the gene with an overexpression approach and gene depletion is potentially more informative from this perspective.…”
Section: The Spatial Organization Of Chromosomes: Chromosome Conformasupporting
confidence: 75%
“…A good example is the recent protein eQTL analyses of serum urokinase plasminogen activator receptor (suPAR) levels (Portelli et al, 2014). uPAR has been identified as an asthma susceptibility gene (Barton et al, 2009) and has been shown to be differentially expressed in the airways (Stewart, Nijmeh, Brightling, & Sayers, 2012) and blood (Portelli et al, 2014) in asthma patients. The receptor exists as a glycosyl-phosphatidylinositol (GPI)-linked receptor and is involved in a wide range of functions including migration, proliferation and adhesion and is also involved in fibrinolysis (Portelli et al, 2014).…”
Section: Protein Eqtl Can Provide Novel Insight Beyond Cis and Trans mentioning
confidence: 99%
“…RNA profiling of AECs revealed that the gene whose expression in these cells was most affected by the absence of TNFR1/2 was Plaur, which encodes uPAR, a serine protease receptor involved in the generation of plasmin from plasminogen. Previous genetic (34) and biological (43,44) evidence has strongly implicated uPAR in asthma, particularly in severe, nonatopic asthma. Our current work shows that Plaur expression in AECs is dependent on TNF signaling responses in those cells.…”
Section: Tnf Signaling Responses Contribute To Aec Transcriptional Rementioning
confidence: 99%
“…21,22 We hypothesized that endogenous production of uPAR in uPA-overexpressing HSAEpiC cells may be necessary to sustain EMT. To test this hypothesis, we transfected uPA-overexpressing and control HSAEpiC cells with the uPAR shRNA silencing vector, pSuper-shuPAR.…”
Section: Upa Overexpression Induces Emt In Hsaepic Cellsmentioning
confidence: 99%